Pengaruh Beban Tugas Akademik dan Dukungan Sosial Terhadap Tingkat Burnout Mahasiswa Pendidikan Administrasi Perkantoran - Dian Zahwa Oktaviani; Marsofiyati Marsofiyati (Lembaga Pengembangan Kinerja Dosen, 2025)
Academic workload is a responsibility in education that must be completed by individuals, while social support is assistance that helps fulfill emotional, physical, and social needs. Academic burnout is the physical, emotional, and mental exhaustion caused by excessive academic pressure over a prolonged period. This study aims to identify the influence of academic workload and social support on burnout among Office Administration Education students at the State University of Jakarta. The analysis results show that academic workload has a significant influence on burnout (coefficient 0.653), while social support is not significant (value 0.125). An R-Square of 83.3% indicates that both variables explain 83.3% of burnout variations, with the remaining influenced by other factors such as economic conditions and intrinsic motivation.